Effectivity of aroma, light, and al’quran therapy to enhance driver’s level of awareness in Malaysia - Yohan Kurniawan (2010)
The effectiveness of fatigue therapy toward drivers was measured with three treatments using an aroma therapy (the odor of lemon, cananga and stinking egg), sparkling lights therapy and Al ‘Quran therapy. This repetitive experiment design was done in a driving simulator. The level of fatigue was measured using a fatigue questionnaire. The drivers (N = 20 males) were asked to stop their driving when they got tired, and the result shows that the driving duration was shorter when the stinking egg therapy was given compared to the other therapy treatments. Driving period by using Quran therapy was longer than aroma therapy and the sparkling light therapy. The therapy of stinking odor strongly stimulates the sleepy driver to awaken compared to the other treatments. The therapy of listening to Al ‘Quran passages increased persistence and keep the drivers to be awake when they took a long drive compared to the other treatments.